Research portfolio - Garosas, Elfriede S (Rhodes University, Faculty of Education, Department of Education, 2004)
[From Introduction]. The study involved student teachers and teacher educators providing me with information concerning their perception and understanding of the BETD broad curriculum and needlework and clothing syllabus. The above mentioned are the people who are involved in teacher education thus I found it relevant to have their opinions and understanding of the documents. The contextual analysis has engaged me in exploring a possible area of research specialisation for the two years during the course of studies with Rhodes University; this will serve as an introduction to the particular research to be done through the course of my studies. The focus of this report includes the following: "¢ A critical analysis of (BETD) needlework and clothing syllabus in relation to the BETD broad curriculum; "¢ A socio-historic and economic analysis of the context for which the syllabus has been designed; "¢ An analysis of the learners for whom the syllabus is designed. In this case students provided their autobiography; "¢ An analysis ofthe learning environment in which the syllabus operates; the physical structure and resources. Together with the critical analysis of the curriculum a small scale survey intending to find out the following information from the student teachers and teacher educators was conducted. "¢ The extent to which the broad curriculum differs from the previous teacher education on issues related to democracy, quality, access, cultural bias, racial discrimination and classes (level of economic status); "¢ How the needlework and clothing syllabus addresses the needs of student teachers; "¢ Whether the needlework and clothing syllabus has enough content; "¢ The challenges facing teacher education and how they can be addressed; "¢ Whether the needlework and clothing syllabus is learner-centred; "¢ Whether the syllabus is gender oriented or biased. This evaluation framework provides a foundation for later investigation
Keywords: Education -- Namibia; Curriculum planning -- Namibia; Home economics -- Study and teaching -- Namibia; Teaching -- Namibia; College teachers -- Training of -- Namibia; Universities and colleges -- Curricula -- Namibia